Philosophical Significance of the Way, Experience, and Silence in the Context of Camino de Santiago - Mizdrak, Inga (Verbum vitae, 2024)
The problem addressed in the article refers to an attempt to present the phenomenon of the way, experience, and silence in the context of pilgrimage to Santiago de Compostela in modern times. The objective is to present what is popularly referred to as Camino as a dynamic and evolving perspective on human spirituality in relation to the challenges of modern times. The main thesis of the proposed study is that this type of pilgrimage offers an alternative to the phenomenon of increasing secularization. The key concepts related to the Camino were discussed and interpreted using the methods of analysis and synthesis in order to present the anthropological vision of the human being developed by Karol Wojtyła and Józef Tischner. An outline of their ideas reveals the deeper meaning of the way and experience. The main conclusion following from the analysis of the issue is that, by embarking on the Camino route, an individual is enabled to take a more in-depth look at his or her own condition, his or her perspective on relationships with others, contemplation, and new opportunities to organize and develop his or her own spirituality.